Analisis Penetapan Ujrah Menurut Ekonomi Islam Studi Kasus BMT UGT Sidogiri Glenmore - Anggita Desy Mayang Rianti; Sofi Faiqotul Hikmah (JPSDa: Jurnal Perbankan Syariah Darussalam, 2021)
This study aims to find out 1) How is the analysis of determination of the case study of hajj funding financing case study at BMT UGT Sidogiri Glenmore?, 2) What is the Islamic Economic perspective on the determination of the ujroh in financing the hajj bailout fund at BMT UGT Sidogiri Glenmore?This type of research uses the type of field research, with a descriptive qualitative approach, and the data collection technique used is a direct interview technique. The conclusion from the results of this study is related to the determination of ujrah which is in accordance with DSN fatwa no. 09 / DSN-MUI / IV / 2000, that the community's need to obtain the benefits of an item often requires another party through an ijarah agreement, namely the transfer of use rights (benefits) contract for an item / service within a certain time with lease payments (ujroh), without must be followed by the transfer of ownership of the goods themselves. Then that the contract (ijarah) is in accordance with Islamic teachings. DSN considers it necessary to stipulate a fatwa on the ijarah agreement to be used as a guideline by the LKS.